Modeling and Control of Energy Conversion during Underground Coal Gasification Process - Laciak, Marek; Kačur, Ján; Durdán, Milan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The present book contains nine articles that were accepted and published in the Special Issue "Modeling and Control of Energy Conversion during Underground Coal Gasification Process" of the MDPI Energies journal. This book focuses on the energy conversion processes in underground coal gasification (UCG), as well as on the modeling and control of this process. The articles published in this book can be divided into three thematic parts of research in the field of underground coal gasification technology: the first part is the impact of technology on the environment, the second is research (studies) on the coal areas and coal properties of UCG technology, and the third is the monitoring, modeling, and control processes within UCG. We hope that this book will be interesting and useful for workers and researchers in the field of underground coal gasification technology, as well as for those who are interested in the mathematical modeling and control of this process.